1994
DOI: 10.1128/jcm.32.3.846-847.1994
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of epidemic and nonepidemic methicillin-resistant Staphylococcus aureus strains on the basis of protein A gene polymorphism

Abstract: The X region of the protein A gene of Staphylococcus aureus contains a highly polymorphic sequence which is composed of repeats of 24 bp. We used amplification by PCR to investigate whether this region could be used to discriminate between epidemic and nonepidemic methicillin-resistant S. aureus (MRSA) strains. Most epidemic MRSA strains (24 of 33) harbored more than seven repeats, while most nonepidemic MRSA strains (10 of 14) contained seven or fewer repeats. It is conceivable that a longer X region results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 7 publications
7
75
1
1
Order By: Relevance
“…PCR amplified the highly polymorphic sequence of the X region of the protein A gene, which is composed of a variable number of 24-bp repeats. Strains were analyzed as described previously by Frenay et al with some modifications (8). An isolated bacterial colony on a blood agar plate was suspended in 1 ml of sterile water and centrifuged for 1 min at 15,500 ϫ g. The pellet was resuspended in 200 l of Instagene matrix (Bio-Rad Laboratories) and incubated at 56°C for 15 to 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplified the highly polymorphic sequence of the X region of the protein A gene, which is composed of a variable number of 24-bp repeats. Strains were analyzed as described previously by Frenay et al with some modifications (8). An isolated bacterial colony on a blood agar plate was suspended in 1 ml of sterile water and centrifuged for 1 min at 15,500 ϫ g. The pellet was resuspended in 200 l of Instagene matrix (Bio-Rad Laboratories) and incubated at 56°C for 15 to 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Roberts and Gaston found a lower level of protein A expression and a higher level of coagulase expression in EMRSA strains than in sporadic strains (21). Frenay and coworkers tried to discriminate between EMRSA and SMRSA strains on the basis of protein A gene polymorphism (8). They reported that strains with more than seven repeats in the X region of the protein A tended to be epidemic, while the presence of seven or fewer repeats was indicative of a nonepidemic MRSA strain.…”
mentioning
confidence: 99%
“…Antibiogram and phage typing are commonly used in epidemiological study, however, the former is often inadequate to differentiate strains, and the latter is limited by reproducibility and the frequent occurrence of untypable strains [3,4]. Molecular typing procedures were developed to overcome the disadvantages of these conventional methods, and include chromosomal DNA analysis by pulsed-field gel electrophoresis (PFGE) [3,27], ribotyping [28,29], and RFLP analyses of staphylococcal genes amplified by PCR [6,8]. Among these, RFLP analysis after PCR amplification may have an advantage in its ease for practice and interpretation of results, and therefore may be suited to routine examination in a hospital.…”
Section: Disc-ussionmentioning
confidence: 99%
“…although they do not necessarily exhibit consistent results [2][3][4]. It has recently been recognized that mnolecular typing has an advantage over conventional typing based on phenotypic markers, such as biotypes or antimicrobial susceptibility [5][6][7][8], in terms of both its reproducibility and discriminatory power. N. KOBAYASHI Coagulase gene typing was designed as one of the molecular methods readily applicable to clinical laboratories [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while CRP analysis has been used successfully in several epidemiological studies of S. aureus (9,13), one study has indicated that it is insufficient as a sole method for the typing of staphylococcal isolates (21). Nevertheless, by combining CRP analysis with other fast PCR-based analytical techniques such as protein A gene typing (6) or inter-IS256-PCR typing (5), this methodology may be able to meet the needs of health departments. In any event, the development of a fast and highly discriminatory typing method for S. aureus remains an important focus.…”
Section: Discussionmentioning
confidence: 99%